Factors Influencing Industry 4.0 Adoption among Small and Medium Enterprises in Southeast Vietnam: An Integrated Technology-Organization-Environment-Resource-Based View-Diffusion of Innovation Framework - Van, Phạm Quang; Thu, Võ Thanh (International Review of Management and Marketing, 2026)
The Industry 4.0 paradigm transforms how firms manufacture products, create value in digitalized markets, and sustain competitive advantage; nevertheless, the use of fourth industrial revolution technology among Vietnamese SMEs is confined. This work investigates the determinants of Industry 4.0 adoption for SMEs in Southeast Vietnam based on the integrated framework of the Technology–Organization–Environment (TOE) model, the Resource-Based View (RBV), and the Diffusion of Innovation (DOI) theory. A sequential mixed-methods design was utilized. After refining and validating the measurement scales using qualitative inquiry and pilot studies, data were collected from 416 SME executives and analyzed with PLS-SEM. The findings suggest that external support plays the largest role for the Industry 4.0 adoption process, followed by support from top management, risk-taking culture, financial capability, human resource capability, competitive pressure, and perceived relative advantage. Conversely, technological complexity is detrimental to the technology adoption process. The culture of risk-taking acts as a mediator between organizational resources and technology adoption, while impacts of support from leadership and risk-taking culture are heightened in contexts of market turbulence. Theoretically, it contributes to the TOE literature by combining RBV and DOI perspectives, highlighting how organizational resources are converted into adoption outcomes through a risk-taking organisational culture. Practically, it provides policy-makers, industrial associations and SME managers with insights into promoting the accelerated digital transformation and stronger implementation of Industry 4.0.